Evaluation of vegetative growth and behaviour of coffee seedlings (Coffea arabica) infected or not by a Meloidogyne exigua population from the northwest of the Rio de Janeiro state - Dias, Pedro Paulo; Vieira, Henrique Duarte; Barbosa, Dimmy Herllen Silveira Gomes; Viana, Alexandre Pio; Gonçalves, Wallace; Andrade, Wander Eustáquio de Bastos (Coffee Science - ISSN 1984-3909)
Coffee is one of the main commodities of the State of Rio de Janeiro and, among other problems, the damage caused by Meloidoyne exigua Goeldi, 1887, hinders the expansion of coffee in the State. The production of seedlings by hypocotyledonary grafting solves this problem, since it combines the resistance of Coffea canephora Pierre ex Froehn. to M. exigua to the quality and productivity of C. arabica L. Despite practiced in São Paulo, the hypocotyledonary grafting has not been validated in the conditions present in the State of Rio de Janeiro and neither the resistant genotypes were tested with populations of M. exigua belonging to the State, potentially different because of the genetic variability of this species. In this work was evaluated under greenhouse conditions the development of seedlings of four genotypes of coffee in non-grafted or grafted on ‘IAC Apoatã 2258’, infested or not with M. exigua. ‘IAC Obatã’ in non-grafted and ‘Iapar 59’ grafted had stood out with good vegetative growth. ‘IAC Obatã’, ‘IAC Red Catuaí 144’ and ‘IAC Tupi’ were susceptible to the fluminense population of M. exigua, while ‘IAC Apoatã 2258’ and ‘Iapar 59’ showed resistance, although allowed small reproduction of the nematode.